Implementasi Pelayanan Online Single Submission (OSS) di Mal Pelayanan Publik Kabupaten Sleman - Suwanto Suwanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
With the emergence of Law Number 11 of 2020 concerning Job Creation, the relationship between the central government and regional governments is regulated and reorganized, especially in terms of administering business licensing in the regions. Job creation is about efforts to create jobs through facilitation, protection and empowerment of micro, small and medium enterprises as well as increasing the investment cycle and ease of doing business so that investors and entrepreneurs can easily obtain the required permits easily. The Sleman Regency Government through the Investment Service and One-Stop Integrated Services (DPMPTSP) has implemented business licensing through the Online Single Submission system, which is an information technology-based licensing that integrates regional and central licensing in order to facilitate domestic business activities. By using it will make it easier for business actors in the stages of business requirements, business licenses and business operations. Licensing data is obtained in the identity of the Business Identification Number (NIB). NIB is one of the requirements for obtaining assistance for business actors in obtaining various assistance and licensing services issued by the OSS Institution.